Análisis del diseño de un sistema de gestión de calidad para la empresa “RECARGAS INKTEC” de acuerdo con la norma ISO 9001 - versión 2015 - Patiño Reyes, Jimmy Alexander (Universidad Antonio Nariño, 2022)
In the city of Barrancabermeja an important economic growth is recognized, therefore, companies are constantly improving to be at the forefront of the development that is lived and attempts to overcome a pandemic that could put development on hold for more than six months.